Status Report: NFCS implementation in Kenya - Dinku, Tufa; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The International Research Institute for Climate and Society (IRI) of the Columbia Climate School has been supporting the National Framework for Climate Services (NFCS) process in Kenya. In this report, the current status of NFCS development and implementation in the country is briefly summarized, alongside next steps towards actualizing the implementation of the framework in Kenya.